PROGRAM BIMBINGAN KARIR UNTUK MENGEKSPLORASI MINAT KARIR PESERTA DIDIK TUNARUNGU - Pardi, Pardi; Herdi, Herdi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study explores the career interests of deaf students at SMALB Pangudi Luhur using a qualitative method with a descriptive approach. The research population consists of students from SMALB Pangudi Luhur, with a sample of 30 tenth-grade students. Data were collected using the Strong Interest Inventory (SII) instrument, which identifies career interest types based on John Holland's theory of vocational choice. The results indicate that deaf students have varied career interests, yet most lack clear career planning. The developed career guidance program aims to help students recognize their talents, interests, abilities, and the courage to make appropriate career choices. This program, formulated based on SII assessments, includes basic services, individual interest and planning, responsive services, and system support. Through an inclusive approach involving all stakeholders, the program strives to ensure that every student has access to explore their full potential in life. This study underscores the importance of targeted and focused career guidance to support the development and well-being of deaf children, enabling them to achieve success in education and their careers.